2010
DOI: 10.1093/eurheartj/ehp572
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of sinus rhythm in patients with heart failure and permanent atrial fibrillation undergoing cardiac resynchronization therapy: a longitudinal observational study

Abstract: One in every 10 HF patients with permanent AF may experience SRR after CRT. Baseline EDD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…Last but not least, AVJ ablation is the most powerful predictor of sinus rhythm resumption in permanent atrial fibrillation patients treated with CRT [13]. The conversion from atrial fibrillation to sinus rhythm even after many years of CRT seems to be related to the higher biventricular pacing (BVP) observed in ablated patients, and consequent volume and 'electric' reverse remodeling.…”
Section: Key Pointsmentioning
confidence: 99%
“…Last but not least, AVJ ablation is the most powerful predictor of sinus rhythm resumption in permanent atrial fibrillation patients treated with CRT [13]. The conversion from atrial fibrillation to sinus rhythm even after many years of CRT seems to be related to the higher biventricular pacing (BVP) observed in ablated patients, and consequent volume and 'electric' reverse remodeling.…”
Section: Key Pointsmentioning
confidence: 99%
“…150 msec, a left atrial diameter of ! 50 mm and AV junction ablation (6). Although this patient had only one of these predictors, CRT successfully restored the sinus rhythm in combination with oral amiodarone therapy initiated one month after device implantation.…”
Section: Discussionmentioning
confidence: 83%
“…24 These studies suggest that atrial fibrillation burden declines in the first 3 to 6 months after CRT-D implantation 25,26 and resolves altogether in some patients. 27 Patients may also experience better outcomes with a high degree of biventricular pacing or atrioventricular junction ablation. 28–30 A meta-analysis of 23 observational studies found that atrial fibrillation was associated with a higher risk of nonresponse and all-cause mortality, but only a quarter of the patients had atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%